Pengaruh Kompensasi, Motivasi, Stres Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Grosir Sembako CV Jembatan Hitam (Studi Pada Karyawan Grosir Sembako CV. Jembatan Hitam, Ganjar Asri, Kota Metro) - Ayuningtias, Icha; Suryadi, Suryadi (Universitas Muhammadiyah Metro, 2022)
ABSTRACT The most important asset for an organization is human resources so that every company or organization must work together optimally to produce quality products. Where the management is required to use a good management system and can be used as a tool to improve the performance of its employees. The formulation of the problem in this study was